A cross-sectional survey on benzodiazepine use among older people in an Italian region (Italian Journal of Public Health, 2005)
Background. Benzodiazepines are among the most commonly prescribed drugs in Italy and they are oftenused inappropriately according to guidelines for their rational use.The aim of this study was to investigate the prevalence and pattern of use of benzodiazepine amongst thegeneral population aged 65-84 years in the Friuli-Venezia Giulia Region, in North-East Italy.Methods. A total of 40 general practitioners participated in the study. Two data sources were used in theresearch. The first was the Health Search Database, the second was a short questionnaire administered bythe general practitioners to the 65 to 84 year old patients attending their surgeries for any reason during thestudy period. Data on the use of benzodiazepines between 1stFebruary and 31stJuly 2001 were extracted fromboth the Health Search Database using drug prescriptions and the questionnaires.Results. Of the 10,468 patients aged 65-84 years with complete demographical data in the generalpractitioners’ patient lists, 2,369 subjects used benzodiazepines, hypnotics and over the counter drugs. Overallprevalence of benzodiazepine use was 21.5% (95% confidence interval: 19.8-23.1%). Of the benzodiazepineusers, 66.9% consumed a short-intermediate half-life and 33.1% a long half-life benzodiazepine. Most patientstook benzodiazepines at night (68.2%), less frequently in the daytime and at night (23.7%), or in the daytimeonly (8.1%). Most users (89.2%) said they had been taking benzodiazepine for years.Conclusions. Benzodiazepine use was associated with patient characteristics, such as being female, usinganalgesics or antidepressants and the presence of a chronic disease especially cancer or chronic heart failure.
Keywords: benzodiazepine; cross-sectional study; older people; anxiolytic; hypnotic